2021
DOI: 10.3389/fpls.2021.735192
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci Hotspots Affecting Agronomic Traits and High-Throughput Vegetation Indices in Rainfed Wheat

Abstract: Understanding the genetic basis of agronomic traits is essential for wheat breeding programs to develop new cultivars with enhanced grain yield under climate change conditions. The use of high-throughput phenotyping (HTP) technologies for the assessment of agronomic performance through drought-adaptive traits opens new possibilities in plant breeding. HTP together with a genome-wide association study (GWAS) mapping approach can be a useful method to dissect the genetic control of complex traits in wheat to enh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 92 publications
3
9
0
Order By: Relevance
“…A frequently used threshold was established at -log 10 P > 3, as previously reported in the literature (Condorelli et al, 2018;Mangini et al, 2018;Sukumaran et al, 2018;Rufo et al, 2021;Wang et al, 2021a). Confidence intervals (CI) for marker-trait associations (MTA) were estimated for each chromosome according to the LD decay reported by (Rufo et al, 2019) using the formula reported by (Chardon et al, 2004).…”
Section: Gwas Analysismentioning
confidence: 99%
“…A frequently used threshold was established at -log 10 P > 3, as previously reported in the literature (Condorelli et al, 2018;Mangini et al, 2018;Sukumaran et al, 2018;Rufo et al, 2021;Wang et al, 2021a). Confidence intervals (CI) for marker-trait associations (MTA) were estimated for each chromosome according to the LD decay reported by (Rufo et al, 2019) using the formula reported by (Chardon et al, 2004).…”
Section: Gwas Analysismentioning
confidence: 99%
“…Interestingly, in QTL hotspot 1B.6, a Cytochrome c oxidase gene was upregulated in leaves and spikes (TraesCS1B01G413200). This gene was previously found to be upregulated in spikes by Rufo et al [ 42 ] in a GWAS for yield and vegetation indices-related traits using the same panel of landraces but also including a panel of modern wheat cultivars.…”
Section: Discussionmentioning
confidence: 93%
“…Field experiments were conducted under rainfed conditions in Gimenells, Lleida, northeast Spain, during 2016, 2017 and 2018 harvesting seasons, as reported in Rufo et al [ 42 ]. The experiments consisted of a non-replicated augmented design with two replicated checks, the cultivars ‘Anza’ and ‘Soissons’, at a ratio of 1:5 between checks and tested genotypes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop drought tolerant varieties it is essential to understand the genetic basis of these complex traits [ 4 ], thus identification of quantitative trait loci (QTL) and genes for important agronomical traits such as grain yield and its components is a key component of crop improvement programs [ 5 ]. To date, a large number of QTLs associated with yield component traits and grain yield under water deficit condition [ 1 , 2 , 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and normal condition [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] have been identified on all 21 wheat chromosomes.…”
Section: Introductionmentioning
confidence: 99%